Emotional control and physical activity in children aged 6 to 12 years - Marcillo Mármol, Daniela Margarita (MENTOR revista de investigación educativa y deportiva, 2026)
At an early age, work on emotional control should be prioritized because it is important for proper inter- and intrapersonal development. Physical activity helps children develop empathy with their peers through expression and movement. The objective of this research was to systematize the theoretical and methodological assumptions that underpin emotional control and physical activity in children aged 6 to 12. A methodology based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol will be used, and documents that meet inclusion and exclusion criteria will be consulted in databases such as Dialnet, Recyt, Redalyc, and Scielo. The results obtained demonstrated that physical activity contributes positively to emotional control in children. Furthermore, physical education teachers are recognized as promoters of intelligent physical activity, that is, those who consider the socio-emotional aspect of their classes. The conclusions highlighted the importance of developing information on the topic and recommended non-competitive physical activity to promote positive emotions.